Analysis of the Role of Export Risk Management and Financing Policy Effectiveness on the Competitiveness of the Agricultural Industry in Indonesia - Judijanto, Loso; Sono, M Gifari; Priyana, Yana (Westscience Press, 2025)
This study investigates the role of export risk management and financing policy effectiveness in enhancing the competitiveness of Indonesia's agricultural industry. Using a quantitative approach, data were collected from 120 respondents, including stakeholders in the agricultural export sector, through a structured questionnaire employing a five-point Likert scale. The data were analyzed using SPSS version 25, with results indicating that both export risk management and financing policy effectiveness have significant positive impacts on competitiveness. Export risk management emerged as the stronger predictor, highlighting the importance of proactive strategies in mitigating trade risks. The combined influence of these factors explains 67% of the variance in competitiveness, underscoring their synergistic effect. The findings emphasize the need for policymakers and industry leaders to prioritize integrated risk management frameworks and enhance access to sector-specific financing solutions to support sustainable growth in agricultural exports.